EFFECTS OF PLANT GROWTH REGULATORS ON THE MORPHOGENESIS OF CAULIFLOWER CURD TRANSVERSE THIN CELL LAYER EXPLANTS - Nhựt, Dương Tấn; Vinh, Bùi Văn Thế (Vietnam Journal of Biotechnology, 2011)
Transverse thin cell layers (tTCLs) from mature curd of Cauliflower  (Brassica oleracea var. botrytis) were cultured  on  Murashige  and  Skoog  medium  supplemented  with  different  types  of  plant  growth  regulators (PGRs)  at  various  concenfrations.  The results  were  recorded  after  6 weeks  of  culture.  The presence  of 2,4-dichlorophenoxy-acetic  acid  (2,4-D)  at  0.1  -  1.0  mg  1"' resulted  in  callus  formation,  while  roots  formed  in culture medium supplemented with  0.5 -  1.0 mg 1"' NAA (naphthalene  acetic acid). When  l-phenyl-3-(l,2,3-thiadiazol-5-yl)-urea (TDZ) was added to culture medium at 0.2 - 0.6 mg 1"', shoot clusters regenerated directly from the  edge  of  explants.  Shoots  initiated  in  the  presence  of  TDZ,  but  without  stem  elongation  and  leaf formation.  In order to  obtain normal plant  development,  clumps  of regenerated  shoots were fransferred onto PGR-free  MS medium. Approximately 26 shoots with normal stem elongation developed from each tTCL after 2 weeks. Rootmg was obtained by fransferring shoots to MS medium supplemented with 0.4 mg 1"' NAA and 0.2  mg  r'   Kinetin.  Regenerated  plants  with  adventitious  roots  were  fransferred  to  soil.  The  results demonsfrated  that the choice of PGRs is of significance  in determining the morphogenesis  of cauliflower curd tTCL explants